2019
DOI: 10.1242/jeb.198424
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric resistance training and β-Hydroxy-β-methylbutyrate free acid affects muscle PGC-1α expression and serum irisin, nesfatin-1 and resistin

Abstract: The hypothalamus controls metabolism and feeding behaviour via several signals with other tissues. Exercise and supplements can change hypothalamic signalling pathways, so the present study investigated the influence of eccentric resistance training and β-hydroxy-β-methylbutyrate free acid supplementation on PGC-1α expression, serum irisin, nesfatin-1 and resistin concentrations. Thirty-two male rats (8 weeks old, 200±17 g body mass) were randomly allocated to control, β-hydroxy-β-methylbutyrate free acid supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Chondrocytes were cultured between 1 and 3 passages to avoid loss of the chondrocyte phenotype. According to the previous study ( Tine Kartinah et al, 2018 ; Shirvani et al, 2019 ), chondrocytes were pretreated with irisin (8880-IR-025, R&D Systems, Minneapolis, MN, United States) dissolved in culture media at different physiological concentrations (0, 5, or 10 ng/ml) for 1 h based on the synovial fluid irisin concentrations in rats and then incubated with or without IL-1β (10 ng/ml) for 24 h to induce chondrocyte inflammation and the involvement of signaling pathways. Chondrocytes were divided into the following groups: control group, in which the same amount of serum-free medium was added; IL-1β group; IL-1β + irisin (5 ng/ml) group; IL-1β + irisin (10 ng/ml) group.…”
Section: Methodsmentioning
confidence: 99%
“…Chondrocytes were cultured between 1 and 3 passages to avoid loss of the chondrocyte phenotype. According to the previous study ( Tine Kartinah et al, 2018 ; Shirvani et al, 2019 ), chondrocytes were pretreated with irisin (8880-IR-025, R&D Systems, Minneapolis, MN, United States) dissolved in culture media at different physiological concentrations (0, 5, or 10 ng/ml) for 1 h based on the synovial fluid irisin concentrations in rats and then incubated with or without IL-1β (10 ng/ml) for 24 h to induce chondrocyte inflammation and the involvement of signaling pathways. Chondrocytes were divided into the following groups: control group, in which the same amount of serum-free medium was added; IL-1β group; IL-1β + irisin (5 ng/ml) group; IL-1β + irisin (10 ng/ml) group.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the results of this study indicate that CaHMB supplementation amplifies the effect of RT on body fat reduction by activating FNDC-5/irisin pathway related thermogenesis in WAT. Although eccentric RT associated with HMB free acid increased the serum irisin levels in rats [ 32 ], our study is the first to demonstrate reduction in body fat in response to RT associated with CaHMB linked to activation of the FNDC-5/irisin pathway.…”
Section: Discussionmentioning
confidence: 81%
“…However, the combined treatments increased the gene expression of IL-6 in gastrocnemius, FNDC-5 in soleus muscles, and irisin concentration in WAT. RT has been reported to increase FNDC-5, irisin and UCP-1 [ 5 , 48 ], and HMB has been suggested to increase lipid oxidation in adipose tissue via increase in the gene and protein expression of hormone-sensitive lipase [ 49 ], mitochondrial biogenesis [ 25 ] and activation of PGC-1 α [ 31 , 32 ]. Additionally, HMB associated with polyphenols was suggested to activate sirtuin signalling and the FNDC-5/irisin pathway, resulting in significant increases in fatty acid oxidation in adipocytes and myotubes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, RT alter irisin levels and gene expression of fibronectin type III domain-containing protein 5 (FNDC-5) in the muscle and UCP-1 in the WAT 42,43 , and HMB has been suggested to increase lipid oxidation in adipose tissue via increase in the gene and protein expression of hormone-sensitive lipase 44 , mitochondrial biogenesis in myocites 45 and activation of the PGC-1α 46 . Shirvani et al 47 demonstrated that supplementation with HMB-FA associated with RT for 8 weeks increased muscle strength, gene expression of the PGC1-α in skeletal muscle and plasma irisin concentration.…”
Section: Hmb and Resistance Trainingmentioning
confidence: 99%